The Skincare Selection Application That Best Suits The Method Analytical Hierarchy Process (AHP) - Ilka Zufria; M. Fakhriza; Nur Nofrizal Agustina Srg (Sean Institute, 2021)
The number of beauty and care products is widespread outside, the more skin problems people experience . Various problems of this disease are also caused by allergies due to the use of various beauty products and taking care of the skin from products on the market . Therefore, we need a system that can help choose good skincare according to skin type using the Analytical Hierarchy Process (AHP) method. The application that will be made for the selection of facial foam, moisturizer, and mask with criteria, namely oily skin, normal skin, dry skin, sensitive skin and combination skin, this application is expected to solve the problem of choosing skincare more effectively and precisely. The application of this application uses a waterfall system development, built using the PHP programming language, and bootstrap as a tool interface design to make it look attractive k.